Republic of Latvia : 2017 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Latvia's economic growth eased to 2 percent in 2016, as gross investment contracted significantly by 11.7 percent on the back of lower than expected absorption of European Union (EU) funds. This effect was compounded by a drag from net exports, as import volume growth accelerated markedly, while export growth remained modest. Despite a strong rise in imports, the current account recorded a surplus of 1.5 percent in 2016 as the terms of trade, driven largely by falling energy prices, improved by over 4.7 percent. Growth is expected to pick up to 3.2 percent in 2017 on the back of an accelerated pace of disbursement of EU funds and continued robust private credit growth.